2011
DOI: 10.1177/1350650111401970
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of the influence of loading direction on the thermohydrodynamic behaviour of twin axial groove journal bearing

Abstract: An experimental assessment of the influence of angle between the groove axis and the load line on the thermohydrodynamic behaviour of twin groove hydrodynamic journal bearings has been undertaken. At nine different loading direction angles, the oil-bush interface temperature profiles, oil outlet temperature, maximum bush temperature, total flow rate, and oil flow rate through each groove were measured for variable applied load and oil supply pressure while the feeding temperature was kept constant (40 C). To t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 12 publications
0
47
0
Order By: Relevance
“…To verify the accuracy of the numerical model, the results for a full journal bearing with two axial grooves were compared against the experimental measurements and the numerical simulations of Brito et al . and Arab Solghar et al . Sample results are shown in Figure , which indicate that the THD analysis predictions for temperature and pressure match the measurements fairly well.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…To verify the accuracy of the numerical model, the results for a full journal bearing with two axial grooves were compared against the experimental measurements and the numerical simulations of Brito et al . and Arab Solghar et al . Sample results are shown in Figure , which indicate that the THD analysis predictions for temperature and pressure match the measurements fairly well.…”
Section: Resultsmentioning
confidence: 94%
“…They concluded that heavily loaded twin groove journal bearings might, under certain circumstances, be deleterious for bearing performance. Not only the power loss is normally higher than that of single groove bearings but also the cooling effect of feeding oil might be poorer, under certain combinations of high eccentricity and low feeding pressure, namely due to negative flow rate inception in one of the grooves, as already confirmed in for a bearing with the plane of grooves located at ±90° to the load line and in for a bearing with the grooves located at various angles with the load line.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…9 The increase of load angle was found to decrease the flow rate at the upstream groove and to increase the flow rate at the downstream groove. Negative flow rate was detected in either groove (although, naturally, never simultaneously) for wide ranges of load.…”
Section: Introductionmentioning
confidence: 96%